How to Shift Consumer Willingness to Use the Emerging Technologies On Omnichannel - Sunisa Junsawang; Wornchanok Chaiyasoonthorn; Mariusz Urba_ski; Singha Chaveesuk (My University, 2022)
This paper examines factors that show how to shift consumer willingness to use emerging technologies on omnichannel. The goal was to understand what parameters influence consumer tendency to adopt developing technologies onOmnichannel.The study was motivated by a desire to better understand the challenges that emerging technologies face, as they are not widely used due to concerns about operability, safety, and privacy, in contrast to established technologies.The study utilized UTAUT2 and ECM Models to create a triangulation model.Furthermore, the study used empirical data to develop 11 hypotheses, nine constructs, and one moderating factor by Structural Equation Modeling (SEM).The study was a quantitative survey using both online and offline shoppers in Thailand.A structured questionnaire was used to obtain primary data from a sample size of 520 people between May 12 and August 15, 2021.The result indicated that all the hypotheses were supported, and the variables were seen to have direct and indirect influences on the acceptance model.Finally, this paper proposes that combining the Unified Theory of Acceptance and Use of Technology, Expectation-Confirmation Model, Service Quality, and Personal Innovativeness would allow for a better understanding of factors of Willingness to Use Emerging Technologies.
Keywords: Omnichannel; Consumer Retail Behavior Studies